2020
DOI: 10.1096/fj.202001034rr
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA sequencing reveals the landscape of early female germ cell development

Abstract: Meiosis initiation is a crucial step for the production of haploid gametes, which occurs from anterior to posterior in fetal ovaries. The asynchrony of the transition from mitosis to meiosis results in heterogeneity in the female germ cell populations, which limits the studies of meiosis initiation and progression at a higher resolution level. To dissect the process of meiosis initiation, we investigated the transcriptional profiles of 19 363 single germ cells collected from E12.5, E14.5, and E16.5 mouse fetal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 42 publications
10
58
0
Order By: Relevance
“…The scRNA-seq analysis has been widely applied to studying the germ cells or gonadal development in organisms in recent years. However, up to now, most investigations on ovarian transcriptome focus mainly on limited species, including human (Liu et al, 2009;Zhang et al, 2018), monkey (Wang et al, 2020), mouse (Dean, 2002;Zhao et al, 2020), zebrafish (Zhu et al, 2018), and fly (Slaidina et al, 2020), which revealed the remarkable interspecies variations and conservations during ovarian development across phyla.…”
Section: Single-cell Transcriptome Of Asian Seabassmentioning
confidence: 99%
“…The scRNA-seq analysis has been widely applied to studying the germ cells or gonadal development in organisms in recent years. However, up to now, most investigations on ovarian transcriptome focus mainly on limited species, including human (Liu et al, 2009;Zhang et al, 2018), monkey (Wang et al, 2020), mouse (Dean, 2002;Zhao et al, 2020), zebrafish (Zhu et al, 2018), and fly (Slaidina et al, 2020), which revealed the remarkable interspecies variations and conservations during ovarian development across phyla.…”
Section: Single-cell Transcriptome Of Asian Seabassmentioning
confidence: 99%
“…The expression of TFs associated with meiosis initiation, including Msx1, Msx2, Cdx2, Sox4, Gata2, and Bmyc, was markedly upregulated at the pre-leptotene stage of PGCs. Meanwhile, Dmrtc2 and Taf4b expression was upregulated in the late meiotic stage, whereas Taf9b expression was upregulated at the late meiotic stage of PGCs [50]. The expression of pluripotent genes, Nanog and Oct4, and their associated genes, Dppa2 and Dppa4, was downregulated in PGCs at E11.5 [51].…”
Section: Findings From Scrna-seq Studies In Pgcsmentioning
confidence: 95%
“…These subtle transcriptional changes cannot be detected using traditional global RNA sequencing methods. However, recent single-cell sequencing approaches have been successfully used to uncover other discreet spatial and temporal regulators of meiosis (Niu and Spradling 2020;Zhao et al 2020). Both studies performed fine-scale analyses of the germ cell meiotic transcriptomes covering the E12.5 and E14.5 (Niu and Spradling 2020) and E12.5, E14.5, and E16.5 (Zhao et al 2020) time points, respectively.…”
Section: Oogonia Enter Meiosis Shortly After Sex Determinationmentioning
confidence: 99%
“…However, recent single-cell sequencing approaches have been successfully used to uncover other discreet spatial and temporal regulators of meiosis (Niu and Spradling 2020;Zhao et al 2020). Both studies performed fine-scale analyses of the germ cell meiotic transcriptomes covering the E12.5 and E14.5 (Niu and Spradling 2020) and E12.5, E14.5, and E16.5 (Zhao et al 2020) time points, respectively. Another unreviewed preprint also analyzed germ cell transcriptomes between E10.5 and E16.5 (Mayère et al 2021).…”
Section: Oogonia Enter Meiosis Shortly After Sex Determinationmentioning
confidence: 99%
See 1 more Smart Citation